2014
DOI: 10.1128/jvi.03118-13
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus Gn and Gc Glycoproteins Self-Assemble into Virus-Like Particles

Abstract: f How hantaviruses assemble and exit infected cells remains largely unknown. Here, we show that the expression of Andes (ANDV) and Puumala (PUUV) hantavirus Gn and Gc envelope glycoproteins lead to their self-assembly into virus-like particles (VLPs) which were released to cell supernatants. The viral nucleoprotein was not required for particle formation. Further, a Gc endodomain deletion mutant did not abrogate VLP formation. The VLPs were pleomorphic, exposed protrusions and reacted with patient sera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…These mutants were all expressed correctly and reached the cell surface (S5 Fig), but syncytium formation and cell entry by the corresponding pseudotyped SIV particles was abrogated (Fig 4D and 4E). In order to further explore whether trimerisation of the mutants is impaired, we made virion-like particles (VLPs) of Andes virus [60] harboring the mutations D11A and H14Y in Gc. We harvested VLPs from cells transfected with wild type Gn/Gc or with wild type Gn and the mutant Gc, which secreted VLPs at similar levels (S5 Fig).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These mutants were all expressed correctly and reached the cell surface (S5 Fig), but syncytium formation and cell entry by the corresponding pseudotyped SIV particles was abrogated (Fig 4D and 4E). In order to further explore whether trimerisation of the mutants is impaired, we made virion-like particles (VLPs) of Andes virus [60] harboring the mutations D11A and H14Y in Gc. We harvested VLPs from cells transfected with wild type Gn/Gc or with wild type Gn and the mutant Gc, which secreted VLPs at similar levels (S5 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…VLPs were harvested from supernatants of 293FT cells transfected with the pI.18/GPC wt or the different mutant constructs at 48 h post-transfection as previously established [60]. Subsequently, VLPs were concentrated by ultracentrifugation for one hour at 135,000 g and detected by reducing SDS PAGE and western blot using anti-Gc MAb as described above.…”
Section: Methodsmentioning
confidence: 99%
“…R1074 (R417 in Gc numbering) is the only residue at the base of PUUV sG C stem that maintains side chain intramolecular contacts with domain II and it is highly conserved among hantaviruses (except HNTV and SEOV where it is substituted with lysine of similar properties, S2 Fig). To investigate the role of R1074 in membrane fusion, we introduced an alanine substitution of R1074 in both, PUUV and ANDV GPC in order to test their activity in the available in vitro systems established mostly for ANDV [17, 58]. The R1074A mutants of ANDV and PUUV G C were expressed as the wild type proteins, localized on the cell surface and assembled into virus like particles (VLPs) (S4A Fig).…”
Section: Resultsmentioning
confidence: 99%
“…However, not all 3 proteins are necessary for VLP formation. Rodrigo Acuna et al showed that Gn and Gc co-expressed Gn and Gc in mammalian cells assemble into VLPs, suggesting that the NP protein is not necessary for VLP assembly (Acuna et al, 2014). VLPs with other members of the Bunyaviridae family can also form after Gn and Gc co-expression (Overby et al, 2006;Mandell et al, 2010).…”
Section: Bunyaviridae Familymentioning
confidence: 99%